Analisis Kinerja Keuangan Pada PT Mayora Indah Tbk - Denura Ghiyats Maulida (Jurnal Akuntansi Publik Nusantara, 2024)
In this study, researchers will analyze the financial performance of PT Mayora Indah Tbk using financial ratio analysis, including liquidity, solvency, profitability, and activity ratios. Quantitative descriptive is the type of research used in this study. Documentation technique is the method used in this study with data sources derived from the financial statements of PT Mayora Indah Tbk for 2019-2020 sourced from www.idx.co.id. The results of the study show that the percentage of the liquidity ratio increased from 2019 to 2020, indicating that the company's financial performance is in good and solid condition in terms of liquidity and its ability to meet short-term obligations. However, the solvency ratio shows a decline in financial performance during the same period. On the other hand, the profitability ratio reflects good performance in 2019 and the ability to maintain profitability in 2020. For the activity ratio, in 2019 the company's financial performance was considered quite good, but in 2020 it decreased due to several factors.